Graphene on Chromia: A System for Beyond‐Room‐Temperature Spintronics (Adv. Mater. 12/2022). Issue 12 (24th March 2022) - He, Keke; Barut, Bilal; Yin, Shenchu; Randle, Michael D.; Dixit, Ripudaman; Arabchigavkani, Nargess; Nathawat, Jubin; Mahmood, Ather; Echtenkamp, Will; Binek, Christian; Dowben, Peter A.; Bird, Jonathan P.
Abstract : Spintronics There has long been interest in exploiting the excellent spin coherence in graphene for applications in spintronics. In article 2105023, Keke He, Jonathan P. Bird, and co‐workers demonstrate robust spin conduction in graphene, well beyond room temperature. This enhanced performance derives from pronounced spin–orbit coupling, introduced when a chromia substrate is used to break the natural symmetry of the carbon lattice.